The Three Thruths: Philippe Mousket, Matthew Paris, the Anonymous Ghibelline of Piacenza and a Battle in 1238 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The essay analyzes three texts that describe the same battle fought near Piacenza in 1238: the work of the Italian Anonimo Piacentino, the Frenchman Philippe Mousket and the Englishman Matthew Paris. The analysis shows very different visions of chivalry, linked to different social and cultural contexts of the authors.
Keywords: Chivalry; 13th century; Philippe Mousket; Matthew Paris; Anonimo Piacentino